2011
DOI: 10.1093/cvr/cvr107
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins induce nitric oxide generation in human pulmonary artery endothelial cells

Abstract: These results indicate that NTs acutely modulate pulmonary endothelial NO production and contribute to relaxation of the pulmonary vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 59 publications
3
66
1
2
Order By: Relevance
“…BDNF and NT-3 induce relaxation of porcine pulmonary arterial rings, through activation of the endothelial nitric oxide synthase (Meuchel et al, 2011). Suppression of TrkB or TrkC expression via siRNA as well as functional blockade of p75 NTR suggest a role of both Trk and p75 NTR receptors in these effects (Meuchel et al, 2011). In our ongoing studies in rat or human pulmonary arteries, we show that NGF does not induce rat or human pulmonary arterial contraction or relaxation by itself.…”
Section: Pulmonary Hypertensionmentioning
confidence: 82%
See 1 more Smart Citation
“…BDNF and NT-3 induce relaxation of porcine pulmonary arterial rings, through activation of the endothelial nitric oxide synthase (Meuchel et al, 2011). Suppression of TrkB or TrkC expression via siRNA as well as functional blockade of p75 NTR suggest a role of both Trk and p75 NTR receptors in these effects (Meuchel et al, 2011). In our ongoing studies in rat or human pulmonary arteries, we show that NGF does not induce rat or human pulmonary arterial contraction or relaxation by itself.…”
Section: Pulmonary Hypertensionmentioning
confidence: 82%
“…A role for neurotrophins in the control of the pulmonary arterial tone was recently proposed, through activation of the p75 NTR receptor (Xu et al, 2008). BDNF and NT-3 induce relaxation of porcine pulmonary arterial rings, through activation of the endothelial nitric oxide synthase (Meuchel et al, 2011). Suppression of TrkB or TrkC expression via siRNA as well as functional blockade of p75 NTR suggest a role of both Trk and p75 NTR receptors in these effects (Meuchel et al, 2011).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…The NO-insensitive dye 4-aminofluorescein diacetate (DAF-4) (5 M) was used as a negative control for NO detection. Cells were imaged as described previously (Meuchel et al, 2011) by using a real-time fluorescence imaging system (MetaFluor; Molecular Devices, Sunnyvale, CA) mounted on a Nikon (Tokyo, Japan) Diaphot inverted microscope, with a 40ϫ/1.3 numerical aperture oil immersion lens (Fryer Instruments, Edina, MN). Cells were initially perfused with 2.5 mM Ca 2ϩ Hanks' balanced salt solution, and baseline fluorescence was established.…”
Section: Downloaded Frommentioning
confidence: 99%
“…2A). Sensitivity of DAF-2 for NO within BECs per se was determined as described recently for pulmonary artery endothelial cells (Meuchel et al, 2011) by constructing an empirical curve of amplitudes of fluorescence changes (difference from baseline at 15 min) using a range of MAHMA-NONOate concentrations (1 nM to 10 M). Concentrations of 1 nM MAHMANONOate showed minimal changes over baseline fluorescent levels and were comparable with vehicle controls.…”
Section: Er Expression In Human Becsmentioning
confidence: 99%
“…In accordance with this, animal studies showed that interaction between the endothelial cells as well as cardiac contractility could not be established in the absence of BDNF in the prenatal period, followed by early postnatal death (12). Moreover, in human pulmonary artery endothelial cells BDNF substantially increased nitric oxide levels by activating Akt and endothelial nitric oxide synthase, indicating that neurotrophins acutely modulate pulmonary endothelial nitric oxide production and contribute to relaxation of the pulmonary vasculature (27).…”
Section: Bdnf Blood Level and Its Associatesmentioning
confidence: 97%